A Rabbit Clinical Trial of Xylazine-Ketamine vs. Fentanyl-Ketamine for General Anesthesia - Hameed, Falah Mahmood; Kadhim, Fateh; Al-Tomah, Hayder Mohammed Mohsen; Altaee, Raeed (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The Aim of Study: The current investigation was designed to compare the anesthetic and physiological effects of ketamine with different pre-anesthetics protocol. Methods: A total of twelve healthy male rabbits were chosen for the clinical anesthetic trial. Animals were presented to the faculty of veterinary medicine at Kerbala University for skin wound procedures and separated into two equal groups 6 rabbits each (group A and group B). Rabbits in group A were administered an intramuscular injection of xylazine (10mg/kg BW) followed by ketamine (50 mg/kg I.M) after 10 minutes. while those in group B were injected with fentanyl (0.04 mg/kg BW, I.M) first plus ketamine (50 mg/kg I.M) after 10 minutes. The physiological and anesthetic parameters to assess the complications that associated with anesthetic, were recorded and analyzed. Results: The level of induction and recovery varied significantly (P<0.05) among the groups. Compared to group B, group A had a considerably (P<0.05) shorter induction time. Furthermore, group A's mean time for losing pedal reflex revealed a substantial (P<0.05) decrease. Between-group differences in the responses to the pain test and muscular relaxation were statistically significant (P<0.05). Group A experienced a substantially longer (P<0.05) induction period, surgical anesthetic duration, and recovery period than group B. No rabbits died as a result of the anesthetic or the recuperation. Conclusion: Compared to Fentanyl-ketamine (FK) combination anesthesia, administration of Xylazine with ketamine (XK) apparently does not influence the physiological parameters. Additionally, this method provides a very successful anesthetic procedure for a flawless induction, suitable muscle relaxation, extended anesthesia, and a painless recovery.